2012
DOI: 10.1016/s1734-1140(12)70740-5
|View full text |Cite
|
Sign up to set email alerts
|

Exendin-4 reduces glycemia by increasing liver glucokinase activity: an insulin independent effect

Abstract: Exendin-4 is a stable peptide agonist of GLP-1 receptor that exhibits insulinotropic actions. Some in vivo studies indicated insulin-independent glucoregulatory actions of exendin-4. That finding prompted us to evaluate effects of exendin-4 on liver glucose metabolism. Acute and chronic treatment of exendin-4 resulted in increased hepatic glucokinase activity in db/db mice but not in lean C57 mice. The stimulatory effect of exendin-4 on glucokinase activity was abrogated by exendin 9-39, a GLP-1 antagonist. Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 37 publications
2
28
1
Order By: Relevance
“…Moreover, insulin secretions occurred in a similar manner in all medium concentrations of glucose (2.8, 5.6 and 16.7 mM). One of the effects of exendin-4 is an increase in glucokinase enzyme activity in the liver through a parallel and independent insulin-mediated mechanism [3]. It has been shown that glucokinase can initiate phosphorylation of glucose after it has diffused into liver cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, insulin secretions occurred in a similar manner in all medium concentrations of glucose (2.8, 5.6 and 16.7 mM). One of the effects of exendin-4 is an increase in glucokinase enzyme activity in the liver through a parallel and independent insulin-mediated mechanism [3]. It has been shown that glucokinase can initiate phosphorylation of glucose after it has diffused into liver cells.…”
Section: Resultsmentioning
confidence: 99%
“…A number of drugs are being studied for treatment and prevention of metabolic syndrome, but investigations into pharmaceutical intervention of pancreatic and hepatic function associated with metabolic disturbances have received less attention. Exendin-4 is an United States Food and Drug Administration (FDA) approved glucagon-like peptide-1 that increases insulin-dependent glycogen synthesis and the liver’s glucose uptake [3]. In one study, exendin-4 demonstrated a reduction in ROS generation and an enhancement effect on antioxidant enzyme activity, such as SOD, GPX, and CAT in rats [4].…”
Section: Introductionmentioning
confidence: 99%
“…Although there is little meaningful evidence indicating expression of the GLP-1R in the liver (24,31), there are several reports of GLP-1-mediated regulation of hepatic glucose production in a manner separate from its ability to suppress glucagon release and, intriguingly, independent of insulin (32)(33)(34)(35). We therefore measured EGP rates to investigate whether a GLP-1R-dependent mechanism accounts for regulating glycemia in Gcgr 2/2 animals.…”
Section: Glp-1r Ablation Increases Egp In Insulinopenic Gcgr-null Micementioning
confidence: 99%
“…Most importantly, incretins are known to stimulate insulin secretion during hyperglycemia. In addition, glucagon secretion may be reduced, and some studies have suggested that incretins may have direct effects on tissues such as the liver, increasing insulin sensitivity (1,10,26) and modifying molecular regulators of hepatic glucose metabolism (3,14,15,45,54), thereby modifying liver glucose production and uptake independently from the effects of changes in insulin secretion. On the other hand, other studies have not observed a direct effect (1,10,26), and our data support the latter conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Although several groups have detected GLP-1 receptor expression in the liver of mice (6), rats (61,64), and humans (24,56), others have been unable to do so across a wide range of species, including the mouse (65), rat (4,19), dog (55), and human (35,62,63). Ex-4 has been shown to increase liver glucokinase activity in hepatocytes isolated from diabetic mice in an insulin-independent manner (14,15). In addition, GLP-1 and Ex-4 have been reported to increase glycogen accumulation in rat hepatocytes, an effect associated with increased and decreased glycogen synthase and phosphorylase activities, respectively (3,45,54), although others were unable to reproduce those results (47).…”
mentioning
confidence: 99%